Contribution of Writing Interest toward Indonesian Language Learning of Students in Vocational High Schools - Faizal Arvianto (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
This research aims to find out how the contribution of writing interest toward Indonesian language learning of students in vocational high schools in the city of Kefamenanu, East Nusa Tenggara province. This study utilised a quantitative method with a correlational approach. Based on the results of data analysis, data on student writing interest was in averaged 74.8% with good category. Based on the calculation results, there was a correlation of about 0.290 and was included correlation coefficient in the low category. The result of the significance t-test shows that t count score was 3.248. Referring to the results of the study, it can be concluded that there is a positive and significant correlation between the writing interest toward Indonesian language learning of the students of grade X of vocational high schools in Kefamenanu.